MANAJEMEN RISIKO FATAL DI PT. FREEPORT INDONESIA - Eman Widijanto; Sony Suryanto; Fransiscus Novento (PERHAPI, 2023)
PT Freeport Indonesia (PTFI) operates underground copper-gold mines (block cave and open stoping mining methods) located in the remote highlands of Papua, Indonesia, about 3,500 km east of Jakarta, Indonesia. The rugged terrain with extreme elevation changes, highly varied weather, variety of geological condition and complex mining-processing activities create challenging situation to manage safe and productive mine operation.From safety statistics performance, the Total Reportable Incident Rate (TRIR) and severity rate have declined over time, however achieving zero fatality consistently is still significant challenge for the team.Fatal Risk Management (FRM) is one of PTFI’s safety programs to eliminate and reduce serious injuries and fatalities. This paper elaborates the history of the FRM program, implementation challenges, digitalization transformation program and future improvement to ensure safety of the workers and continued achievement of desired mine-mill production.